Resilience of the primary healthcare system: perspectives of German stakeholders at primary care interfaces during the second wave of the COVID-19 pandemic - Litke, Nicola; Weber, Sophia; Breckner, Amanda; Roth, Catharina; Peters-Klimm, Frank; Wensing, Michel; Stengel, Sandra (Frontiers in Medicine, 2024)
Introduction Worldwide, the primary care sector played a key role in coping with the challenges of the SARS-CoV-2 pandemic. Methods The aim of this study was to explore the resilience of the German primary healthcare system during the second wave of the pandemic from the perspective of identified interface stakeholders, i.e., representatives of hospitals, district offices, and medical associations. Qualitative data from interviews and focus groups were analyzed according to a resilience framework. Results The main findings include a gap in knowledge transfer, unstructured allocation of responsibilities, and a resulting unregulated flow of patients. Social brokers supported care coordination and knowledge transfer. The response to the capacity to cope with uncertainties was slow and chaotic at the system level and heterogeneous at the individual level. Building on previous relationships fostered functioning communication, while competition in primary care was identified as a barrier to resilience. Conclusion Implications for further research and for strengthening the resilience of primary care can be derived based on this study.